THE ROLE OF THE THIRD PARTY IN RESOLVING THE CONFLICT IN ACEH - Hardi Alunaza SD; Mentari . (Universitas Pendidikan Muhammadiyah Sorong, 2021)
This paper is aims to answer how Henry Dunant Centre (HDC) and Crisis Management Initiatives (CMI) can be engaged to facilitate the settlement of the conflict in Aceh between the Indonesian government and GAM. In international relations, the role of official diplomacy or first track diplomacy is not always successful in resolving conflicts, especially internal conflicts. Therefore, internal conflicts are usually resolved not through official institutions but by international non-governmental organization (NGO) known as un-official diplomacy or track two diplomacies. Flexibility and neutral nature make NGO becomes easier to be involved and accepted by all parties without being tied to the protocol or the fear of lack of recognition in sovereignty and legitimacy. NGO focus full concentration to the problems he was facing made him better able to understand the problems and relatively unencumbered by limitation of time. The risk faced when facilitating or mediating role he did fail was not too heavy, for the NGO itself and for the parties involved in the conflict. It became reason why HDC and CMI more accepted as third party actor to resolve internal conflict than any other official actors. By using peacemaking as framework of conflict resolution offered by Johan Galtung, this paper shown HDC and CMI successfully held some mediation and negotiation between GAM and RI in January 2005 by brings the result with the signing of a Memorandum of Understanding (MoU) GAM and Government of the Republic of Indonesia in August 2005. The signing of MoU draft is an achievement that very important and essential for conflict resolution in Aceh.